Catalytic oxidation of diclofenac by hydroxylamine-enhanced Cu nanoparticles and the efficient neutral heterogeneous-homogeneous reactive copper cycle. (15th April 2019) - Xiang, Wei; Zhou, Tao; Wang, Yifan; Huang, Mingjie; Wu, Xiaohui; Mao, Juan; Lu, Xiejuan; Zhang, Beiping
Abstract: This study has demonstrated that hydroxylamine (HA) could greatly enhance Cu nanoparticles (nCu) in activating molecular oxygen and significantly elevate the diclofenac (DCF) degradation rate about two orders of magnitude in neutral circumstances. Effects of several important parameters on the DCF degradation such as nCu loading, HA dosage, pH and reaction temperature were investigated in the nCu/HA/O2 system. Multiple examinations revealed that the reactive Cu(III) species instead of OH would be predominant in the nCu/HA/O2 system, despite their similar DCF degradation pathways. Based on a HA-enhanced copper cycle depending on the pristine Cu 0 @Cu(I) (hydro)oxides core-shell structure, the heterogeneous-homogeneous reaction mechanism was proposed. It included solid-liquid interfacial and bulk reactions, e.g. heterogeneous activation of O2 by Cu(I) to produce H2 O2 and homogeneous Cu(I)-catalytic generation of Cu(III) from H2 O2 . Further quantitative investigation of the main reactive species in the cycle revealed that the Cu(I) regeneration instead of the O2 activation would be rate-limited. Besides, nCu could be recycled to effectively degrade DCF in four consecutive cycles in the raw neural nCu/HA/O2 system. It suggested that the nCu/HA/O2 system with a more efficient copper cycle would be a good alternative Fenton-like system in treating neutral recalcitrant organic wastewaters. Graphical abstract: Image 1 Highlights: HA elevated neutral nCu/O2 system in oxidizing diclofenac two orders of magnitude. HA-enhanced heterogeneous-homogeneous Cu cycle on core-shell Cu 0 @Cu(I) was proposed. Cu(III) instead of OH. would be the predominant oxidant in the nCu/HA/O2 system. Cu(I) regeneration instead of O2 activation would be rate-limited in the Cu cycle. Recycled nCu could be used for 4 consecutive cycles in effectively degrading DCF.